2007
DOI: 10.1016/j.dnarep.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

UvrA and UvrB enhance mutations induced by oxidized deoxyribonucleotides

Abstract: Oxidatively damaged DNA precursors (deoxyribonucleotides) are formed by reactive oxygen species. After the damaged DNA precursors are incorporated into DNA, they might be removed by DNA repair enzymes. In this study, to examine whether a nucleotide excision repair enzyme, Escherichia coli UvrABC, could suppress the mutations induced by oxidized deoxyribonucleotides in vivo, oxidized DNA precursors, 8-hydroxy-2´-deoxyguanosine 5´-triphosphate and 2-hydroxy-2´-deoxyadenosine 5´-triphosphate, were introduced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…These results seem surprising, considering that one key function of the NER system is to limit mutations by repairing DNA lesions. Our results are, however, consistent with previous findings in E. coli , where decreased mutation frequencies were reported in uvrA and uvrB mutants after treatment with oxidized deoxyribonucleotides, while mutation rates were unaffected in a uvrC mutant [31]. Under non-damage-inducing conditions, E. coli mutants in uvrA uvrB and uvrC exhibited a lower mutation rate [24].…”
Section: Discussionsupporting
confidence: 92%
“…These results seem surprising, considering that one key function of the NER system is to limit mutations by repairing DNA lesions. Our results are, however, consistent with previous findings in E. coli , where decreased mutation frequencies were reported in uvrA and uvrB mutants after treatment with oxidized deoxyribonucleotides, while mutation rates were unaffected in a uvrC mutant [31]. Under non-damage-inducing conditions, E. coli mutants in uvrA uvrB and uvrC exhibited a lower mutation rate [24].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the lack of sequence homology, the endonuclease domain has an RNase H-like fold. We established the methods of purification of UvrC from T. thermophilus (ttUvrC; TTHA1568), and Hori et al developed an in vitro reconstitution system of NER using purified ttUvrA, ttUvrB, and ttUvrC [131]. The ttUvrABC system can recognize a (6-4) thymine dimer and excise the affected strand; however, it does not excise a strand containing 8-hydroxy-2′-deoxyguanine or 2-hydroxy-2′-deoxyadenine [131].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…UvrA contains three zinc ions. It has been reported that ttUvrA and ttUvrB can recognize bulky adducts, such as tetramethylrhodamine and tetramethylrhodamine ethyl ester, and (6-4) pyrimidine dimer [113, 131]. Furthermore, it has been shown that ttUvrA can interact with the ATL protein, but the physiological significance of this interaction remains unclear [37].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…The E. coli UvrA and UvrB proteins, which are involved in nucleotide excision repair, enhanced the mutations induced by 8-OH-dGTP and 2-OH-dATP by an unknown mechanism(s) [48].…”
Section: Roles Of Dna Repair Proteinsmentioning
confidence: 99%